Soignés, soignants en perte d’équilibre - Gervais, Richard (Criminologie, 1988)
Working in the health service of the Montreal Prevention Centre, the author presents the observations he made while there. The constant increase in psychiatric cases since 1976, in both number and severity, according to the author, is the result of deinstitutionalization by the Department of Social Affairs. The clientele, suffering from a psychic pathology, expresses its suffering and hopelessness in delinquent activity. Given the limits on intervention in this type of milieu, the ambiguity of the laws and restricted facilities, prison is not appropriate for the psychiatric offender. Victim of the power struggle between the government departments and social organizations, he bears the stigma of the table imposed on wards of the court.